Exhaust Emissions Reduction Of Diesel Engine Fueled With Emulsified Palm Oil Methyl Esters - Amir, Aziz; Wong, Chung Siong; R., Mamat; Hagos, F. Y. (Trans Tech Publications, Switzerland, 2014)
An emulsion fuel is one of an alternative method that has been used to reduce exhaust emissions from diesel engine. However, water emulsion of biodiesel was not properly explored in diesel engine. In this work, the effect of water concentration in palm oil diesel emulsions (POD) [POD is palm oil Methyl ester] on exhaust emissions of a four-cylinder diesel engine was investigated. The engine speed was set at 2500 rpm and loads at 20, 40 and 60 %. Water-in-POD emulsions were prepared using ultrasonic emulsifier by mixing POD fuel with 5, 10 and 20 % of water by volume. Results of exhaust emissions for POD and their emulsion were compared with ordinary diesel (OD) fuel. The experimental results show that, the increasing water concentration in POD decrease the NOx and PM simultaneously. POD-water emulsion is a promising alternative fuel for reducing emissions from diesel engines without any engine modification.